Socio Economic and Livelihood Analysis of the People in Garhkundar-Dabar Watershed of Central India - Palsaniya, D.R.; Singh, Ramesh; Tewari, R.K.; Yadav, R.S.; Dwivedi, R.P.; Kumar, R.V.; Venkatesh, A.; Kareemulla, K.; Bajpai, C.K.; Singh, Rajendra; Yadav, S.P.S.; Chaturvedi, O.P.; et al. (Indian Journal of Agroforestry, 2020)
The studies on socio-economic, livelihood and plant species having considerable economic significance in the livelihood of people of Dabar-Garhkundar watershed are presented in this paper. The present investigation was conducted in Dabar-Garhkundar watershed of Tikamgarh, M.P. representing typical physiography and economy of Bundelkhand region. Approximately 895 people are directly dependent on the watershed and having 2648 animal resources of which 57.2% are goat, 16.8% sheep, 11.3% buffaloes and only 4.8% cattle. The watershed area has predominance of people belonging to other backward class (49.3%) followed by scheduled castes (28.3%), scheduled tribes (16.1%) and general category (6.4%). Marginal and small land holdings, together comprises 86.3% and rest 13.7% are medium with no large land holdings in the watershed area. The occupation structure of the watershed people shows that nearly 19.5% population derives its livelihood from agriculture including animal husbandry, while 56% people dependent on agriculture as well as labour work in and around the watershed. Nearly 21% derive their subsistence solely from labour activities. The percentage of people employed in government services is 1.2 while 2.3 per cent people were engaged in other occupations like masonry work, driving, tailoring, pot making, carpentering, etc. The communities living in watershed have immense knowledge about plant wealth and are dependent on flora for their social and livelihood needs. During the study, 22 plant species used for edible purposes; 7 plant species for extraction of gum, tannin, dyes and insecticidal properties; 6 plant species for making ropes, baskets, mats, brooms, fibers and thatching houses; 3 plant species for making country liquor; 12 plant species for fodder; 5 plant species for fencing and 8 plant species for fuel wood, timber and making agricultural implements were recorded from the watershed area.